1989
DOI: 10.1139/b89-239
|View full text |Cite
|
Sign up to set email alerts
|

Climate and annual ring growth of black spruce in some Alberta peatlands

Abstract: DANG, Q. L., and LIEFFERS, V. J. 1989. Climate and annual ring growth of black spruce in some Alberta peatlands. Can. J.Bot. 67: 1885-1889. The long-term relationship between climate and tree-ring growth in black spruce (Picea mariana (Mill.) B.S.P.) was determined in two peatland sites near Slave Lake, Alberta. At each site, 15 dominant-codominant black spruce were sampled for tree-ring growth at 30 cm height. The tree-ring indices for each site were related to precipitation and temperature data from Slave La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0
3

Year Published

1991
1991
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 14 publications
4
37
0
3
Order By: Relevance
“…8; Wilmking and Myers-Smith, 2008) to drought-inhibited growth. Although this poorly drained forest seems an unlikely candidate to experience significant plant drought stress, the combination of root systems limited by a shallow active layer and rapid fluctuations in the water table may lead to periods of reduced water availability (Dang and Lieffers, 1989). Annual growth in Western Canadian black spruce stands has previously be shown to be negatively correlated with temperature and positively correlated with precipitation (Dang and Lieffers, 1989;Brooks et al, 1998).…”
Section: Future Trajectoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…8; Wilmking and Myers-Smith, 2008) to drought-inhibited growth. Although this poorly drained forest seems an unlikely candidate to experience significant plant drought stress, the combination of root systems limited by a shallow active layer and rapid fluctuations in the water table may lead to periods of reduced water availability (Dang and Lieffers, 1989). Annual growth in Western Canadian black spruce stands has previously be shown to be negatively correlated with temperature and positively correlated with precipitation (Dang and Lieffers, 1989;Brooks et al, 1998).…”
Section: Future Trajectoriesmentioning
confidence: 99%
“…Although this poorly drained forest seems an unlikely candidate to experience significant plant drought stress, the combination of root systems limited by a shallow active layer and rapid fluctuations in the water table may lead to periods of reduced water availability (Dang and Lieffers, 1989). Annual growth in Western Canadian black spruce stands has previously be shown to be negatively correlated with temperature and positively correlated with precipitation (Dang and Lieffers, 1989;Brooks et al, 1998). In Interior Alaskan white spruce (Picea glauca) treering width, 13 C and maximum latewood density was shown to be an indicator of tree growth response to temperatureinduced drought stress (Barber et al, 2000).…”
Section: Future Trajectoriesmentioning
confidence: 99%
“…Usually, climate was observed as the key unifying factor determining the growth variability within a large geographical range in stands of mesophilous and dry forests (e.g., Baillie, 1995;Peterson and Peterson, 2001). However, several dendroclimatological studies showed a relatively weak relationship between the annual radial growth of trees and the climate in wetlands, characterised by specific and changeable local conditions (Dang and Lieffers, 1989;Linderholm, 1999;Linderholm and Leine, 2004). We suggest that the growth of A. glutinosa has been affected mainly by local environmental factors, which may also have modified growth responses to key climatic variables over time.…”
Section: Growth Responses Of Alnus Glutinosa To Environmental Conditionsmentioning
confidence: 72%
“…Certains auteurs mentionnent que les températures en fin de printemps et du début de l'été ont un effet positif sur la croissance annuelle (D'Arrigo et al, 1992 ;Hofgaard et al, 1999 ;Schweingruber et al, 1993). D'autres auteurs indiquent plutôt que les températures pour les mêmes périodes ont des effets négatifs (Archambault et Bergeron, 1992 ;Brooks et al, 1998 ;Dang et Lieffers, 1989). Chez l'épinette noire les précipitations au début de l'été auraient un effet positif sur la croissance annuelle (Deslauriers et al, 2003a ;Brooks et al, 1998 ;Dang et Lieffers, 1989 ;Hofgaard et ai., 1999).…”
Section: Mise En Garde/adviceunclassified
“…D'autres auteurs indiquent plutôt que les températures pour les mêmes périodes ont des effets négatifs (Archambault et Bergeron, 1992 ;Brooks et al, 1998 ;Dang et Lieffers, 1989). Chez l'épinette noire les précipitations au début de l'été auraient un effet positif sur la croissance annuelle (Deslauriers et al, 2003a ;Brooks et al, 1998 ;Dang et Lieffers, 1989 ;Hofgaard et ai., 1999). Établir un lien direct entre des températures plus froides et une diminution de la croissance chez les arbres en milieu boréal est donc difficile à faire.…”
Section: Mise En Garde/adviceunclassified